2022
DOI: 10.3389/fphys.2022.1023563
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of cardiac contractility modulation stimulation in conventional 2D and 3D human induced pluripotent stem cell-derived cardiomyocyte models

Abstract: Cardiac contractility modulation (CCM) is a medical device therapy whereby non-excitatory electrical stimulations are delivered to the myocardium during the absolute refractory period to enhance cardiac function. We previously evaluated the effects of the standard CCM pulse parameters in isolated rabbit ventricular cardiomyocytes and 2D human induced pluripotent stem cell-derived cardiomyocyte (hiPSC-CM) monolayers, on flexible substrate. In the present study, we sought to extend these results to human 3D micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…In conclusion, Feaster et al (2022) showed an important novel model for CCM studies supporting our belief that pre-clinical CCM testing in human tissue is necessary for better understanding of underlying CCM mechanisms. LMS form an additional, representative human in vitro platform and might accelerate this journey towards translational CCM and other cardiac devices research.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…In conclusion, Feaster et al (2022) showed an important novel model for CCM studies supporting our belief that pre-clinical CCM testing in human tissue is necessary for better understanding of underlying CCM mechanisms. LMS form an additional, representative human in vitro platform and might accelerate this journey towards translational CCM and other cardiac devices research.…”
supporting
confidence: 56%
“…With great interest we read the article by Feaster et al (2022) , in which they demonstrated cardiac contractility modulation (CCM) stimulation in 3D human engineered cardiac tissue (ECT). The authors showed that the contractile response of 3D ECT to CCM depends on the input parameters of the stimulation pulse, while this response in conventional 2D pluripotent stem-cell derived cardiomyocytes (hiPSC-CMs) remained unaffected.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These approach has been validated in multi-site studies ( Blinova et al, 2018 ) including chronic studies ( Narkar et al, 2022a ), and the best practice recommendations for use of these methods in drug safety assessment has been published ( Gintant et al, 2020 ). More recently, hiPSC-CMs have been proposed as a valid alternative to animal models in the evaluation of cardiac electrophysiology medical devices ( Casciola et al, 2020 ; Feaster et al, 2021 ; Casciola et al, 2022 ; Feaster et al, 2022 ; Narkar et al, 2022b ). Here, we establish a novel, species-relevant, standard laboratory protocol to evaluate and optimize PEF cardiac ablation parameters using hiPSC-CMs in a high-throughput monolayer format.…”
Section: Introductionmentioning
confidence: 99%